STUDY OF THIN-LAYER DRYING OF GRAPE WASTES - Doymaz, I.; Akgun, N. A. (TAYLOR & FRANCIS INC, 2009)
The effect of drying temperature on grape wastes, the solid wastes of the wine and raki production processes, was investigated in a cabinet dryer. Drying experiments were performed three air temperatures of 70, 90, and 110C, at constant air velocity of 1.2m/s, and initial thickness of 1.8cm for grape marc and 2.0cm for grape pulp. Experimental data were fitted to Henderson and Pabis, Page, and logarithmic models, respectively. The performance of these models is evaluated by comparing coefficient of determination and reduced chi-square between the observed and predicted moisture ratios. The statistical analysis concluded that the best model was the logarithmic model. The effective moisture diffusivity varied from 8.5510-10 to 3.3210-9 m2/s over the temperature range. Temperature dependence of the diffusivity was well documented by an Arrhenius-type relationship. The activation energies for grape marc and grape pulp were calculated as 25.41 and 13.74kJ/mol, respectively.
Keywords: Activation energy; Grape marc; Grape pulp; Modeling; Thin-layer drying; ANTIOXIDANT ACTIVITY; KINETICS; OLIVE; POMACE; EXTRACTION; OIL; BEHAVIOR; ANTHOCYANINS; TEMPERATURE; STABILITY; Engineering